Middle-aged healthy women and Alzheimer's disease patients present an overlapping of brain cell transcriptional profile. (15th May 2019) - Sanfilippo, Cristina; Castrogiovanni, Paola; Imbesi, Rosa; Tibullo, Daniele; Li Volti, Giovanni; Barbagallo, Ignazio; Vicario, Nunzio; Musumeci, Giuseppe; Di Rosa, Michelino
Abstract: Exploring sexual dimorphisms in the brain morphology is important for their impact and therapeutic implications for several neurological diseases. The hypothesis that sex could influence the transcriptome of brain cells could be the basis regarding the different response to cognitive decline identified in men and women. In this paper, we analyzed several prefrontal cortices (PFC) microarrays datasets of young/middle-aged healthy subjects and then Alzheimer's disease (AD) patients, according to the sex. The significant transcriptomes were overlapped with the main genes characterizing cells of the central nervous system (CNS) in order to determine the respective weighted percentages of significantly expression gene modulation (WPSEG). We identified differences in brain transcriptional activity between young and middle-aged. In middle-aged women, the WPSEG were higher for the Astrocytes, the Endotheliocytes, and the Microglia. In addition, the sex-matched analysis of transcriptome identified a convergent molecular signature in men and women AD patients. Furthermore, the WPSEG belonging to CNS cells in PFC of healthy middle-aged subjects was correlated to AD profiles according to the sex. Since our results, it is possible to conclude that during the aging the PFC' cells adopt transcriptional strategies sex-dependent that could potentially control the development of neurodegenerative diseases. Graphical Abstract: Unlabelled Image Highlights: There is a difference proportion of gray matter in human men and women. Online microarray datasets could be used to identify the brain cells transcriptome difference between men and women. There are substantial differences in brain transcriptional activity between young and middle-aged men and women. The transcriptome sex-matched analysis identified a convergent molecular signature in AD men and women patients.